Analysis of the Effect of Experiential Marketing on Customer Loyalty Using Customer Satisfaction as a Intervening Variables - Muhammad Idham Khalid; Joko Setyono Setyono (Journal of Business Management and Islamic Banking, 2023)
Research Aims: This research aims to find the influence of experiential marketing, namely sense, feel, think, act, and relate marketing, on customer loyalty at PT. Bank Syariah Indonesia, using satisfaction customer as variable. Methodology: This research is quantitative with a causality study. The sample is composed of 127 customers from Bank Syariah Indonesia. This research uses non-probability sampling as a sampling technique with purposive sampling and a questionnaire with a Likert scale as a data collection technique. As well as using SmartPLS 3.0 software for analysing data using structural equation modelling (SEM). Research Findings: The research reveals that sense and relate variables significantly impact customer satisfaction, while feel, think, and act variables do not. Act has a positive impact on customer loyalty, but other variables have no significant effect. The relationship between satisfaction and loyalty is not significant, and satisfaction cannot mediate the relationship between experiential marketing and customer loyalty. Originalitity: This research details the elements of experiential marketing, such as sense, feel, think, act, and relate, and evaluates their impact on customer satisfaction and customer loyalty Implication: Customer satisfaction can be a critical factor in connecting customer experience to the level of loyalty